Pro Entity Framework 4.0 - Klein, Scott (Apress, 2012)
This book is intended to address two types of developers: those who have never worked with the Entity Framework before, and those who have but are looking at what the ADO.NET 4.0 Entity Framework has to offer. As such, it will cover all aspects of the Entity Framework and, where appropriate, point out the new features and enhancements found in the EF 4.0.